Sistem Informasi pada Hotel Dieng Berastagi Berbasis Web: - Pindi Alpioninta Br. Sembiring Pelawi; Rena Nainggolan; Resianta Perangin-angin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The Information System at the Dieng Berastagi Hotel is a web-based application developed using PHP and MySQL. This system is designed to manage various aspects of hotel operations, including room reservations, guest management, recording payment transactions, and storing customer data. Relevant keywords for this system include: hotels, reservations, guest management, PHP, MySQL. This system utilizes a MySQL database to store and manage information about rooms, guests and payment transactions. PHP was used to develop an interactive and responsive user interface, allowing hotel staff to easily access and manage data. By adopting this technology, Hotel Berastagi can increase its operational efficiency, improve customer experience and improve overall resource management.